2006
DOI: 10.1038/sj.onc.1209862
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active CCK2 receptor splice variant increases Src-dependent HIF-1α expression and tumor growth

Abstract: Gastrointestinal (GI) cancers ectopically express multiple splice variants of the cholecystokinin-2 (CCK 2 )/gastrin receptor; however, their relative contributions to the cancer phenotype are unknown. The aim of this study was to compare the effects of CCK 2 receptor (CCK 2 R) and CCK 2i4sv R expression on cell growth both in vitro and in vivo using a human epithelial cell model, HEK239. In vitro, receptor variant expression did not affect cell proliferation either in the absence or presence of agonist. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 34 publications
5
30
1
Order By: Relevance
“…Exon 7 incorporation is positively regulated by the RNA-binding protein T-STAR (also known as SLM-2) [36]. VEGF expression is itself affected by the alternative splicing products of the Estrogen receptor alpha and the cholecystokin-2/gastrin receptor (CCK 2 R) [37,38]. Another relevant event is the removal of exon 3 of Survivin, which gives it a specific function in promoting angiogenesis [39].…”
Section: Angiogenesismentioning
confidence: 99%
“…Exon 7 incorporation is positively regulated by the RNA-binding protein T-STAR (also known as SLM-2) [36]. VEGF expression is itself affected by the alternative splicing products of the Estrogen receptor alpha and the cholecystokin-2/gastrin receptor (CCK 2 R) [37,38]. Another relevant event is the removal of exon 3 of Survivin, which gives it a specific function in promoting angiogenesis [39].…”
Section: Angiogenesismentioning
confidence: 99%
“…It was also previously reported that the i4sv variant of the CCK-2/ gastrin receptor, which represents a spliced form with intron 4 retention, is constitutively activated and strongly activates Src and FAK kinases compared with the normal form of the receptor (Olszewska-Pazdrak et al, 2002). Other significant effects of the i4sv variant have been noted; for example, CCK-2/gastrin i4sv receptorexpressing cells have elevated expression of HIF-1alpha and VEGF and their injection into mice increased the weight of tumors compared with that of wild-type CCK-2/gastrin receptor (Chao et al, 2007). Although the CCK-2/gastrin receptor participates in carcinogenesis, such as the pancreatic carcinoma described above, little is known about the correlation between the CCK-2/gastrin signaling pathway and the anti-tumor activity of gemcitabine.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 94%
“…Life Sciences j o u r n a l h o m e p a g e : w w w. e l s ev i e r. c o m / l o c a t e / l i f e s c i e signaling pathway downstream of the CCK-2/gastrin receptor (Kowalski-Chauvel et al, 1996;Vatinel et al, 2006;Arsham et al, 2002), and the Src kinase pathway (Chao et al, 2007). It was also previously reported that the i4sv variant of the CCK-2/ gastrin receptor, which represents a spliced form with intron 4 retention, is constitutively activated and strongly activates Src and FAK kinases compared with the normal form of the receptor (Olszewska-Pazdrak et al, 2002).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…59 However, it is unclear if these tumorpromoting effects of CCK 2 Ri4sv observed in experimental models are similar in naturally occurring tumors. In fact, studies assessing the functional effects of CCK 2 Ri4sv were performed mainly with engineered cells exhibiting excessive CCK 2 Ri4sv expression, while original tumors were found to express this variant at very low levels.…”
Section: Cholecystokinin Receptor Typementioning
confidence: 99%